If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 15 = 3y + -3 Reorder the terms: 15 + 6x = 3y + -3 Reorder the terms: 15 + 6x = -3 + 3y Solving 15 + 6x = -3 + 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 6x = -3 + -15 + 3y Combine like terms: 15 + -15 = 0 0 + 6x = -3 + -15 + 3y 6x = -3 + -15 + 3y Combine like terms: -3 + -15 = -18 6x = -18 + 3y Divide each side by '6'. x = -3 + 0.5y Simplifying x = -3 + 0.5y
| -3(-x)-7=1+x | | 28=f-3 | | 6000=4 | | 6(p-8)=-42 | | -30+(150)=X | | 24=2(-x+3) | | 2(3y+4+2)= | | 17+10x-3=-3(x-6) | | 14x+8+10x+28=180 | | 9x+5=12x-19 | | 6-(-7+x)=42 | | 600=2x+3y | | -6(5n+5)=-120 | | 8x-27=4x+33 | | 140=90+m | | 12-4x=-5x+22 | | 12x^2+26x-10=0 | | 2(g+4)+5g-1= | | 3n+28=200 | | 0.75n+1.29=7.00 | | x(2x-5)(x^2-3)(5x^3-8)=0 | | -3x=-5x+22 | | 5x-31=2x+5 | | 7x-36=4x+5 | | 5y-[2(y+1)+2]=7z | | (4.6-8n)0.5=3.8 | | 4n-25=75 | | 2(4-x)+7x=13 | | 4x+4=7x-17 | | x+5.5y=x+y+81 | | 4(5a+16)=16(a-35) | | 3x^4-13x^2=10 |